Science Fiction in Argentina : Technologies of the Text in a Material Multiverse - Page, Joanna, 1974- (Book collections on Project MUSE., 2016)
This book examines an unprecedented range of science fiction texts -- including literature, cinema, theater, and comics -- produced in Argentina from the nineteenth to the twenty-first centuries. These works address themes common to the genre across the industrialized world, including techno-authoritarianism, new modes of posthuman subjectivity, and apocalyptic visions of environmental catastrophe. At the same time, Argentine science fiction is fully grounded in the social and political life of the nation. The texts discussed here explore the impact of an uneven modernization, mass migration, dictatorships, crises in national identity, the rise and fall of the Left, the question of Argentina's indigenous heritage, the impact of neoliberalism, and the most recent economic crisis of 2001. Argentine science fiction is also highly reflexive, debating within its pages the role of science fiction and fantasy in the society of its day, and the nature of the text in a world of advancing technology. This book makes important contributions to our understanding of science fiction as a genre, as well as to materialist theories of cultural texts. It will also interest students and scholars researching the culture, history, and politics of Argentina and Latin America.